Flow immunophenotyping features of crisis phase of chronic myeloid leukemia in childhood: do we really care? - Namrata N Rajkumar; Raghavendra H .V.; Vijay C. Raghu; Lakshmiah K Chinnagiriyappa (International Journal of Medical Research and Review, 2016)
Objective: Chronic leukemias are rare in childhood & CML is extremely rare in children. Imunophenotypic studies have a limited role in the diagnosis of CML but are increasingly being used in CML blast transformation. Purpose of the study was determine the clinical and laboratory and Flow immunophenotyping (FIC) features with Mutational analysis of blast transformation of CML in children.Methods: 11 years analysis was done 187 cases of suspected CML were studied in children and adolescents. Patients were evaluated at KMIO between 2004 to 2015. 97 cases had Bone marrow diagnosis of CML. 22 cases peripheral smear was suggestive of blastic phase CML (20 %) were chosen for the study. Bone marrow confirmation was available in all the cases. Cytogenetics and Molecular confirmation was also available in all cases. FIC was done in 8/22(36%) cases. Mutations were studied in 7 cases.Results: The disease predominantly affected older children more than 10 years 16/22(72 %). Male sex predilection was seen. Gender ratio was 1.4: 1. Most predominant clinical sign was splenomegaly. Leucocyte count>100X109/L was seen in all cases. Peripherals smear suggested CML in all 22cases and bone marrow aspiration confirmed the diagnosis.17 Cases were at diagnosis. 5 Cases progressed to blastic phase from chronic phase. Median year of transformation was 4 years. In 22 cases Phildelphia chromosome was noted and 5 cases revealed additional markers PCR revealed p210 transcript in all cases. In 8 cases in the blastic phase Flow cytometry immunophenotype was done. 5 cases were myeloid blastic phase, single case was mixed phenotype, 2 cases were lymphoid blastic phase.Conclusion: Imatinib highly effective in children with advanced phase of CML. This is the largest, exclusive first reported series of blastic phase of CML in children from a single center. Only 5 cases received Imatinib, All 5cases attained remission; Cases are on follow up and continue to be in remission after a mean of 6 months.